Integrative Analysis of Metallothioneins Identifies MT1H as Candidate Prognostic Biomarker in Hepatocellular Carcinoma - Zhang, Feng; Guo, Shuijiao; Zhong, Wenhui; Huang, Kaijun; Liu, Yubin (Frontiers in Molecular Biosciences, 2021)
Background: Metallothioneins (MTs) play crucial roles in the modulation of zinc/copper homeostasis, regulation of neoplastic growth and proliferation, and protection against apoptosis. The present study attempted to visualize the prognostic landscape of MT functional isoforms and identify potential prognostic biomarkers in hepatocellular carcinoma (HCC). Methods: The transcriptional expression, comprehensive prognostic performances and gene-gene interaction network of MT isoforms in HCC were evaluated via Oncomine, GEPIA, Kaplan-Meier plotter and GeneMANIA databases. Characterized by well prognostic value in three external cohorts, MT1H was specifically selected for potential prognostic biomarker in HCC with various clinicopathological features. Functions and pathways enrichment analyses on MT1H status were performed using cBioPortal, the Database for Annotation, Visualization, and Integrated Discovery (DAVID) databases and ssGSVA method. Results: MT1E/1F/1G/1H/1M/1X/2A were greatly downregulated in HCC. Prognostic analyses elucidated the essential correlations between MT1A/1B/1H/1X/2A/4 attenuation and poor overall survival, and between MT1B/1H/4 downregulation and worse relapse-free survival, and between MT1A/1B/1E/1H/1M/2A/4 downregulation and diminished progression-free survival in HCC. Taken together, these results indicated the powerful prognostic value of MT1H among MTs in HCC. In-depth analyses suggested that MT1H may be more applicable for alcohol-derived HCC and involved in the downregulation of inflammatory pathway, Jak-STAT pathway, TNF pathway and Wnt signaling pathways. Conclusions: MT-specific isoforms displayed aberrant expression and varying prognostic value in HCC. MT1H repression in HCC was multi-dimensionally detrimental to patient outcome. Therefore, MT1H was possibly associated with carcinogenesis and exploited as novel prognostic biomarker and candidate therapeutic target for HCC.